Pacemaker Related Infective Endocarditis from Staphylococcus Lugdunensis: A Case Report - Ward, Michael (Hindawi Publishing Corporation, 2013)
Staphylococcus lugdunensis is a common skin flora not typically associated with infection. There are, however, several cases reported in the literature of Staphylococcus lugdunensis as a causative bacterium of various infections. This paper reports an additional case of pacemaker associated endocarditis with Staphylococcus lugdunensis as the causative bacterium.